Potential causal role of synovial complement system activation in the development of post-traumatic osteoarthritis after anterior cruciate ligament injury or meniscus tear - Holers, V. Michael; Frank, Rachel M.; Clauw, Andrew; Seifert, Jennifer; Zuscik, Michael; Asokan, Sakthi; Striebich, Christopher; Clay, Michael R.; Moreland, Larry W.; Banda, Nirmal K. (Frontiers in Immunology, 2023)
Anterior cruciate ligament (ACL) injury and meniscal tear (MT) are major causal factors for developing post-traumatic osteoarthritis (PTOA), but the biological mechanism(s) are uncertain. After these structural damages, the synovium could be affected by complement activation that normally occurs in response to tissue injury. We explored the presence of complement proteins, activation products, and immune cells, in discarded surgical synovial tissue (DSST) collected during arthroscopic ACL reconstructive surgery, MT-related meniscectomy and from patients with OA. Multiplexed immunohistochemistry (MIHC) was used to determine the presence of complement proteins, receptors and immune cells from ACL, MT, OA synovial tissue vs. uninjured controls. Examination of synovium from uninjured control tissues did not reveal the presence of complement or immune cells. However, DSST from patients undergoing ACL and MT repair demonstrated increases in both features. In ACL DSST, a significantly higher percentage of C4d+, CFH+, CFHR4+ and C5b-9+ synovial cells were present compared with MT DSST, but no major differences were seen between ACL and OA DSST. Increased cells expressing C3aR1 and C5aR1, and a significant increase in mast cells and macrophages, were found in ACL as compared to MT synovium. Conversely, the percentage of monocytes was increased in the MT synovium. Our data demonstrate that complement is activated in the synovium and is associated with immune cell infiltration, with a more pronounced effect following ACL as compared to MT injury. Complement activation, associated with an increase in mast cells and macrophages after ACL injury and/or MT, may contribute to the development of PTOA.